Tourism Management Students' Perceptions on The Use of Moodle Applications in E-Learning - Ni Made Ayu sulasmini; Komang Trisna Pratiwi Arcana (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
The choice of learning media is one of the determining factors for student interest and understanding in a learning process. This study aims to determine the perceptions and barriers of tourism students to the use of Moodle as an online learning application. Student perceptions and barriers were measured through perceived usefulness and perceived ease by using the Technology Acceptance Model (TAM) from Davis (1989). Data was collected through questionnaires to all tourism management students who took online lectures in the odd semester of 2020, using the Moodle application as a Learning Management System. This study shows that the use of the Moodle application provides benefits in terms of providing resources/materials, free time, understanding the topic, increasing independence, increasing discipline, increasing self-confidence, increasing ICT skills, and creating fun learning. Meanwhile, in terms of the ease of use of the Moodle application, students agreed that the ease was felt in terms of using technology, timing, accessing materials, navigating the features contained in Moodle, using language, instructions, assignments, and the lack of technical obstacles in using Moodle. Meanwhile, the identified barriers include: lack of motivation to learn, lack of interaction with other students and lecturers, and internet connection. This study suggests increasing student motivation to learn by designing varied learning modules and able to increase interaction between students and lecturers. This study also suggests investing in internet network supporting infrastructure, in order to provide adequate internet access for students and asynchronous forms of learning.